Dry Bulk Loading and Unloading Services at JIIPE Gresik Port - Wahyudi, Mochammad Nasta Bagus; Priyono, Budi; Prawirosastro, Carlos Lazaro (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2024)
The aim of this thesis research is to understand loading and unloading services and the obstacles faced as well as efforts to minimize these obstacles. The method used is a qualitative research method, where the method is obtained from data based on information or surrounding phenomena in the form of in-depth observations and interviews. The results of this research explain dry bulk loading and unloading services with the procedures and service procedures that apply at JIIPE port. The obstacles faced and efforts to minimize these obstacles are 1) obstacles from waiting for trucks are carried out by coordinating with the truck fleet owner or with the owner of the goods so that there is no waiting time for trucks. 2) obstacles to equipment damage are carried out by means of regular reports regarding equipment maintenance. 3) obstacles from short cargo which is done by checking dry bulk loading and unloading calculations. 4) obstacles from bad weather which is carried out by monitoring weather conditions through ship navigation equipment.